Jawabanmu

2014-08-26T15:55:33+07:00
A. (-3m+4n-6)-(7n-8m-10) = -3m + 4n - 6 -7n +8m + 10 = 5m - 3n + 4
b. (15a+7b-5c)-(-11a-12b+13d) = 15a + 7b -5c +11a +12b +13d = 26a + 19b - 5c + 13d
3 5 3
2014-08-26T16:00:09+07:00
A) (-3m + 4n - 6) - (7n - 8m- 10) = -3m + 4n - 6 - 7n + 8m + 10
                                               = -3m + 8m + 4n - 7n - 6 + 10
                                              = 5m - 3n + 4
b) (15a + 7b - 5c) - (-11a - 12b + 13d)
= 15a + 7b - 5c + 11a + 12b - 13d
= 15a + 11a + 7b + 12b - 5c - 13d
=26a + 19b - 5c - 13d
2 2 2